PRINCIPAL MANAGEMENT IN TEACHING INDEPENDENCE PLATFORM TO IMPROVE JUNIOR HIGH SCHOOL (SMP) TEACHER PERFORMANCE - Timorochmadi, Ferry; Rostini, Deti (Jurnal Konseling Pendidikan Islam, 2025)
This study focuses on the principals' management in utilizing the Merdeka Teaching Platform (PMM) to improve teacher performance at SMPN 43 and SMPN 73 in Bandung City, two schools that won awards as the best users of PMM in West Java. The research objective is to analyze the effectiveness of PMM in improving teacher competence and performance based on the Merdeka Curriculum, as well as to formulate practical strategies for principals in guiding and motivating teachers to be able to implement innovative learning. Using a qualitative approach with a case study method, this study collected data through observation, interviews, and documentation. The theory used refers to Edward Deming's PDCA (Plan, Do, Check, Act) cycle. The results showed that the principal's management in planning, implementing, checking, and following up had run systematically according to Merdeka Belajar policy and education management principles. The principal has succeeded in utilizing PMM as an instrument to improve teacher quality, although there are still obstacles, such as limited access to technology and the IT skills of some teachers, that affect the effectiveness of PMM implementation. Overall, the implementation of PMM has proven effective in promoting a culture of continuous learning in the secondary school environment.